Immune checkpoint blockade in CNS tumors - Reardon, David A. (Henry Stewart Talks, 2016)
Immunotherapy in oncology, CNS immunoprivilege, Glioblastoma (GBM): complexity/redundancy/heterogeneity, “Established” and “Advanced” GBM models, Tumor-specific immune response in GBM, Importance of heterogeneity, Overcoming challenges for durable GBM benefit, Neoantigen mutations, Checkpoint blockade & immunologic memory, GBM vaccines, Personalized neoantigen vaccine (“NeoVax”), Immunotherapy response assessment in neuro-oncology (iRANO), Clinical trials in neuro-oncology, Immunosuppressive mechanisms in GBM, Combination anti-tumor immunotherapy